Птахи давньоруського поселення Ходосівка-Рославське за матеріалами досліджень Північної експедиції 2007 р. - Тайкова, С.Ю. (Археологічні дослідження в Україні, 2009)
The paper is devoted to the analysis of osteological materials found during the archaeological excavations at the settlement Khodosivka-Roslavske in 2007.